Health status and the allocation of time - Timothy J. Halliday; Melinda Podor (Institute for the Study of Labor (IZA), 2009)
In this paper, we quantify the effects of health on time allocation. We estimate that improvements in health status have large and positive effects on time allocated to home and market production and large negative effects on time spent watching TV, sleeping, and consuming other types of leisure. We find that poor health status results in about 300 additional hours allocated to unproductive activities per year. Plausible estimates of the cost of this lost time exceed 10,000. We also find that, for men, better health induces a substitution of market-produced goods for home-produced goods. Particularly, each additional minute spent in home production saves 0.37.
urn:nbn:de:101:1-2009100224
Keywords: I1; J2; 330; Labor supply; time allocation; health; Gesundheit; Zeitallokation; Arbeitsangebot; USA